Transcatheter closure of post myocardial Infarction ventricular septal rupture with the Amplatzer Septal occluder - Adhikari, Chandra Mani; Shrestha, Manish; Timalsina, Birat; Bogati, Amrit; Rokka, Madhu; Acharya, Kiran; Prajapati, Dipanker; Yadav, Dharmanath; Amatya, Ashish Gopal (Nepalese Heart Journal, 2021)
Ventricular septal rupture is a rare yet life threatening complication of acute myocardial infarction. Surgical closure is the treatment of choice however despite surgical intervention mortality remains high. Transcatheter closure of ventricular septal rupture has emerged as a new alternative strategy which is less invasive potentially allowing early hemodynamic stabilization. We report a case of a 60-year-old male with post infarction ventricular septal rupture who was treated with percutaneous closure using an Amplatzer device at Shahid Gangalal National Heart Centre, Nepal.